Biodiversity and relative abundance of insects and spider mites in tree species used as live fences in the Bogotá plateau - LEE, REBECCA A.; CURE, JOSÉ RICARDO; PÉREZ, MARÍA MERCEDES (Revista Colombiana de Entomología, 2000)
Insects and spider miles, both herbivores as well as predators and parasitoids, found in six tree species, Alnus acuminata, Tecoma stans, Pittosporum undulatum, Sambucus Mexicana. Escallonia paniculata andAbutilon prob. striatum used in live fences in the Bogotá plateau, were studied. Two rural environments, farms dedicated to flower production, were chosen, one in the municipality of Sopó and the other in Chía. Sampling was characterized by standardized observation in time and space. directly through observation and collection of material from the trees, as well as indirectly wíth the use of traps. Sampling also included a collection of material for laboratory observation to determine predatory and parasitic relationships. A total of 146 insect and spider mite species were collected in the six tree species, including herbivores, predators, parasitoids, saprofages, and other visitors. with an average of90 species per tree species. Large proportions were predators and parasitoids, many of which have not been registered as such, despite being natural controllers of common crop pests such as spider miles, whitefly, thrips, aphids, and lepidopters. The richness found at all trophic levels shows that live fences are a valuable source of diversity, hosting potential pest herbivorous species as well as their natural controllers.